Surgical resection identified pseudo‐invasion with submucosal dense fibrosis in early colorectal cancer existing beyond the planned endoscopic submucosal dissection line: A case report - Yu Hada; Akiko Ohno; Jun Miyoshi; Ryosuke Kaji; Yasue Fujikawa; Tomoki Horikoshi; Tomoya Hiratsuka; Naohiko Miyamoto; Mitsunori Kusuhara; Yoko Jinbo; Masachika Fujiwara; Junji Shibahara; et al. (DEN Open)
Abstract Pseudoinvasion is a phenomenon in which adenomatous tissue deviates into the submucosa with the mucosal lamina propria in colorectal epithelial tumors. A relatively large, stalked, neoplastic lesion of the sigmoid colon is considered at high risk of pseudoinvasion. A few reports have described endoscopic mucosal resection or polypectomy for colorectal tumors with pseudoinvasion, but the vertical margins were not sufficiently assessed. Because a positive margin can be a risk factor for recurrence, endoscopic treatment for pseudoinvasion should be carefully considered. We herein report a case in which even endoscopic submucosal dissection (ESD) was not adequate for curative resection of pseudoinvasion in early colorectal cancer. The endoscopic findings of a 25‐mm Type 0‐Is lesion in the sigmoid colon suggested a low possibility of carcinoma invasion into the deep submucosa. Although ESD was considered to be indicated in this case, laparoscopic sigmoid colon resection was eventually performed because we observed a broadly pulled muscle layer and an almost undetectable submucosal layer during ESD. The surgical specimen showed that the tumor glands of pseudoinvasion existed beyond the planned ESD dissection line, indicating that the vertical margin would have been positive if we had continued ESD. Whether pseudoinvasion was associated with the infeasibility of ESD remains unclear. This case indicates that diagnosing the presence and depth of pseudoinvasion by magnified endoscopy with narrow‐band imaging is challenging and that preoperative examinations, such as endoscopic ultrasound, may be needed for a tumor with a high risk of pseudoinvasion.